Stepping stones for psychiatry residents who pursue scientific research careers. (June 2013) - Chung, Joyce; Pao, Maryland
Abstract: Advances in areas of neuroscience are highly relevant to psychiatric disorders but there exists a gap between discoveries in neuroscience and the practice of clinical psychiatry. Psychiatry is a field in need of high impact research conducted by physician-scientists who have first-hand experience treating patients with mental illness and who use this clinical knowledge to improve and discover better or novel interventions. This paper focuses primarily on the training of psychiatry residents for successful scientific research careers and what residency programmes and others can do to help them succeed. Changes also need to be made at a regulatory level to enhance the research training and literacy of psychiatry residents. The shortage of psychiatrists who are well trained in basic and translational research can only be remedied if the path to becoming an independent investigator is lined with stepping stones that support success, including during the residency years. Partnerships among funding agencies, professional societies and training institutions can lay the groundwork for our psychiatric trainees to stay on the path to rewarding scientific research careers.